Särkikalojen paikallisuus, ikä ja kasvu Siuntionjoen latvajärvillä - Heikkinen, Salla (2023)
Lake Enäjärvi and Lake Poikkipuoliainen, located in Southern Finland, are eutrophicated and dominated by cyprinids. The lakes are connected to each other by a 2,3 km long River Hulttilanjoki, enabling fish to move between the lakes. The aim of this study was to define the age, growth and maturity of roach (Rutilus rutilus), white bream (Blicca bjoerkna) and bream (Abramis brama). Migration of these three species between the lakes was studied as well. Migration study was conducted by T-bar anchor tagging, meanwhile mortality caused by tagging and handling was studied. Age and growth determination were made from the cleithrum bones. In migration study, only 1,5 % (n = 18) out of all tagged individuals (n = 2178) moved from Lake Poikkipuoliainen to Lake Enäjärvi. Instead, the portion of returned tagged fish (n = 101) was 4,7 % out of all tagged fish. No differences in the mortality caused by tagging and handling between experimental and control groups of bream and white bream were discovered. Instead, the mortality rate of roach in experimental group was 2,2 %, but no mortality was noticed in control group. The growth of roach, bream and white bream was slow in case of both lakes, which is often typical for a lake suffering from dence cyprinid stocks. Management fishing had an effect on growth of some year classes, but no typical higher growth rates of management fishing were found in the long term. In Lake Enäjärvi, the growth of roach and white bream was faster than in Lake Poikkipuoliainen, where instead the stocks of roach and white bream was conducted of smaller-sized individuals. Growth of bream in both lakes has been slowed down, especially in younger age groups. Roach and white bream males reached sexual maturity at younger age in Lake Enäjärvi than in Lake Poikkipuoliainen. In Lake Poikkipuoliainen, male and female breams reached sexual maturity a year younger than in Lake Enäjärvi. The results on the age, growth, sexual maturity and movement of roaches in Enäjärvi and Poikkipuolainen provide important additional information for lake restoration and further planning of biomanipulation.